Visual Preference for Biological Motion in Children and Adults with Autism Spectrum Disorder: An Eye-Tracking Study. - Kaliukhovich, Dzmitry A.; Manyakov, Nikolay V.; Bangerter, Abigail; Ness, Seth; Skalkin, Andrew; Boice, Matthew; Goodwin, Matthew S.; Dawson, Geraldine; Hendren, Robert; Leventhal, Bennett; Shic, Frederick; Pandina, Gahan (Journal of Autism & Developmental Disorders, 2021)
Participants with autism spectrum disorder (ASD) (n = 121, mean [SD] age: 14.6 [8.0] years) and typically developing (TD) controls (n = 40, 16.4 [13.3] years) were presented with a series of videos representing biological motion on one side of a computer monitor screen and non-biological motion on the other, while their eye movements were recorded. As predicted, participants with ASD spent less overall time looking at presented stimuli than TD participants (P < 10–3) and showed less preference for biological motion (P < 10–5). Participants with ASD also had greater average latencies than TD participants of the first fixation on both biological (P < 0.01) and non-biological motion (P < 0.02). Findings suggest that individuals with ASD differ from TD individuals on multiple properties of eye movements and biological motion preference.